Clinical Practice Guidelines and Evidence for the Efficacy of Traditional Japanese Herbal Medicine (Kampo) in Treating Geriatric Patients - Takayama, Shin; Arita, Ryutaro; Kikuchi, Akiko; Ohsawa, Minoru; Kaneko, Soichiro; Ishii, Tadashi (Frontiers in Nutrition, 2018)
Frailty is defined as a state of increased vulnerability to poor resolution of homeostasis following stress, which increases the risk of adverse outcomes such as falls, delirium, and disability in the elderly. Recently in Japan, clinical practice guidelines (CPG) have recommended kampo treatment. We conducted a search for reports on Japanese CPG and kampo medicine in the treatment of symptoms in the elderly. The search was performed using the databases PubMed, Ichushi Web, J-Stage, Japan Medical Publishers Association, Medical Information Network Distribution Service, and CPG containing kampo products in Japan; reports from January 1st, 2012 to October 31st, 2017 were reviewed. Over the past 5 years, nine CPGs have recommended kampo treatment based on the evidence for improvement in skin symptoms, cough, gastro-intestinal dysfunction, urinary dysfunction, and dementia. Treatments with kampo medicine are performed depending on the coexistence of manifestations based on the original kampo concept, i.e., cognitive dysfunction and dementia with sarcopenia showing urinary disorder. Each kampo formula includes multiple crude drugs that have several pharmacological functions; these drugs include alkaloids, glycosides, and polysaccharides. Thus, kampo formula has an effect on multiple organs and coordinates the relationship between the brain, endocrine system, immune system, and skeletal muscles. Kampo treatment can be considered as supporting holistic medicine in elderly individuals with frailty.